Antiretroviral Therapy Adherence among Patients with HIV/AIDS - Tassya Afifah Kustanti; Mohammad Arifin Noor; Suyanto Suyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
The success of Antiretroviral (ARV) therapy is highly dependent on patients’ discipline in taking medication consistently. Various factors, including self-efficacy, are believed to influence the patient’s ability to maintain treatment routines. Poor adherence can reduce therapeutic effectiveness and increase the risk of treatment failure. This study aims to identify the relationship between self-efficacy with ARV therapy adherence among HIV/AIDS patients. This study employed a cross-sectional design involving 64 respondents at RSMD Soepardjo Roestam Semarang. Data were collected using questionnaires and analyzed with the Chi-Square test. Most respondents had low self-efficacy (51,6%), and low ARV therapy adherence (54,7%). Moderate adherence was found in 25% of respondents, while high adherence was found in 20,3%. Statistical analysis showed no significant relationship between ARV adherence (p = 0,291), nor between self-efficacy and adherence (p = 0,566). Other external factors are presumed to influence patients’ adherence levels. and self-efficacy were not significantly associated with ARV therapy adherence among HIV/AIDS patients.